The Relationship between Knowledge and Attitudes of Pregnant Women in RW 02, Sambiroto Village, Semarang, and the Risk of Transmission of COVID-19 - Fitratun Najizah; Shella Dhika Rahmawati; Anisa Mutiara Hanani; Dana Faricha (International Journal of Medicine and Health, 2022)
Coronavirus is an acute pneumonia infection. COVID-19 has spread widely in the world. Based on data from the World Health Organization (WHO), around 215 countries have been infected with COVID-19, including Indonesia. In an effort to reduce the spread of COVID-19, all countries in the world are trying to implement social distancing to prevent the risk of transmission of the virus. Having good knowledge about COVID-19 disease is very important so as not to cause an increase in the number of cases of COVID-19 disease. The important thing to know about COVID-19 is how COVID-19 is transmitted, how to prevent it, treatment, and complications that can occur if someone is infected with COVID-19. Good knowledge and a positive attitude from pregnant women in facing the COVID-19 pandemic can make pregnant women take real action to reduce the risk of contracting COVID-19 so that risks related to decreased immunity and health problems for the baby and mother are not disturbed. The aim of this research is to determine the relationship between knowledge and attitudes of pregnant women in RW 02, Sambiroto Village, Semarang regarding the risk of transmitting COVID-19. The research design used was descriptive correlation with a cross sectional approach, with a sample size of 25 respondents selected using the consecutive sampling method. Data were collected using a questionnaire and analyzed using the Chi Square test. The output of this research is publication in an International Journal.